Pengukuhan Budaya Patriarki dalam Novel Kartini karya Abidah El Khalieqy: Inauguration of Patriarchy in Kartini Novel Written by Abidah El Khalieqy - Nur Halifah (Balai Bahasa Provinsi Papua, 2020)
Kartini novel that written by Abidah El Khalieqy is one of Indonesia's best works inspired by the true story of the hero with the motto